The Principles of Sharia Economic Law in Tasyrihah al Muhtaj Manuscripts by K.H. Ahmad Rifa’i - Hidayani, Fika (KARSA Journal of Social and Islamic Culture, 2018)
This article discuss about the discovery of Tasyrihah al Muhtaj manuscript which contains the principles of sharia economic law that is now developing in Indonesia. This manucsript written since 19 century by K. H. Ahmad Rifa’i, a Mufti from Kalisalak, Batang, Central Java, who was given the tittle of heorism by President Susilo Bambang Yudoyono in 2004. This manuscript written in Pegon (Javanese Arabic) character, and Cirebon Javanese language. Because it had found three manuscripts which have same title, then using plural manucripts method namely base manuscript method, which was chosen one most superior manuscript among others based on language, literature, history aspects. From the contains, the principles of sharia economic law in Tasyrihah al Muhtaj manuscript are usury, ijab, debt, pawn, hawalah, salary, ijarah, and wakalah.